The Eemian Stage interglacial marine transgression in the south-western Baltic region - P. L. Gibbard; K. L. Knudsen (Eiszeitalter und Gegenwart)
Through detailed investigations, three sequences of marine and associated deposits in the south-west Baltic area are shown to represent the Eemian interglacial transgression. Pollen analyses and foraminiferal and ostracod analyses are combined to provide the evolution of relative sea-level change. An independent chronology is established by correlation of the pollen record with that from the Bispingen laminated lake deposits in north Germany. Additional published sites from the area are included in a wider reconstruction of events. Ostracod analyses indicate that freshwater lakes initially existed in the basin prior to the marine inundation. This was followed by an early marine transgression. In the south-west Baltic the first marine ingression took place at the base of regional pollen zone E3, with fully marine conditions established in E4 continuing into the lower part of E5. The regression of the sea during zone E6 was followed by freshwater deposition in E7. The linking of the sequences in the south-west Baltic demonstrates that the Eemian transgression occurred both through northern Germany and through the Danish belts–Kattegat seaway, indicating that connections to the North Sea and North Atlantic were present in the area during the maximum interglacial sea-level highstand.